Side, Türkei. Ein neuentdeckter Kaiserbrief aus Side: Gallienus hilft Side bei einer Getreideknappheit. Die Arbeiten bis 2018 - Nollé, Johannes (e-Forschungsberichte des DAI, 2018)
The Pamphylian city of Side was not only an important seaport and trading town, but could also expect rich yields of grain, wine, oil, and timber from its fertile territory. For this reason the emperor Gallienus was taken by surprise, when in 267 AD a letter arrived, informing him of a wheat-shortage and asking for his help. However, at this same time, the Roman Empire faced the peak of a severe crisis and the emperor was confronted with numerous, almost unsoluble problems. Gallienus, nonetheless, supported the Sidetans through an exemption from the customs duties on imported wheat. Thanks to this measure, the emperor pointed out, the Sidetans were to save considerable sums of money as well as to attract grain ships more easily. We are informed of this noteworthy event in the history of Side by a stele that was recently unearthed by building activities near the ancient port of Side at the very tip of the peninsula. The stele had been erected there in order to inform traders about the customs incentives and to emphasize the emperor’s generosity and affection for his subjects.